2017
DOI: 10.3233/jad-161213
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deprivation Induced Plasma Amyloid-β Transport Disturbance in Healthy Young Adults

Abstract: Sleep deprivation can lead to an elevation of plasma Aβ40 and decrease of the Aβ42/Aβ40 ratio. The underlying mechanisms may be related to increased oxidative stress and impaired peripheral Aβ clearance as pathomechanisms of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 26 publications
3
29
1
Order By: Relevance
“…Preclinical studies that monitor Aβ clearance during sleep using PET radiotracers alongside optical imaging of ISF are needed to corroborate whether Aβ ligands and PET have potential as markers of glymphatic function in the human brain. Future work should also study the extent that elevated ABB in the brain is related to increases in Aβ levels in the peripheral tissue following SD ( 18 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies that monitor Aβ clearance during sleep using PET radiotracers alongside optical imaging of ISF are needed to corroborate whether Aβ ligands and PET have potential as markers of glymphatic function in the human brain. Future work should also study the extent that elevated ABB in the brain is related to increases in Aβ levels in the peripheral tissue following SD ( 18 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have also shown that Aβ levels in the cerebrospinal fluid (CSF) are the highest before sleep and the lowest after wakening, while CSF Aβ clearance was counteracted by SD ( 16 ). However, there are some inconsistencies between animal models and findings in humans ( 17 ), and Aβ increases in human CSF could reflect factors other than ABB increases in the brain itself ( 18 21 ). Notably, the effects of acute SD on Aβ clearance in the human brain have not been documented.…”
mentioning
confidence: 99%
“…This points to a differential effect on plasma A 40: The time of waking seems to increase A 40, whereas sleep fragmentation, as in our study, does not alter the reduction of A 40 overnight, but specifically seems to diminish the reduction of A 42 overnight. 22 In addition to sleep fragmentation, we carefully controlled for other factors that could influence the A 42, among them on-duty setting, time of demand, and years of professional experience. It is notable that years of professional experience was a significant predictor that diminished the decrease of A 42 in the same direction as sleep fragmenta-…”
Section: F I G U R Ementioning
confidence: 99%
“…A growing number of studies have found that sleep disorders may lead to cognitive impairment and accelerate AD pathology, including increased Aβ deposition in the brain [23]. Our recent studies also showed that sleep deprivation induced peripheral Aβ transport dysfunction in young adults [24], and Aβ accumulation in the brain in rats [25]. The underlying mechanism may involve in the oxidative stress in the brain and plasma [26,27].…”
Section: Discussionmentioning
confidence: 99%